Treating Dutch Loanwords in Indonesian as Truncation: A Prosodic Morphology Approach - Muhammad Farris Imadi; SYED JAAFAR, SHARIFAH RAIHAN (Linguistik Indonesia, 2025)
This paper aims to analyze the process of loanword adaptation in Indonesian, focusing specifically on those with foreign suffixes and treating this phenomenon as a truncation process. Traditionally, Indonesian loanwords have been analyzed as undergoing a regular phonological process, as they often involve only a single segmental change. However, in some instances, the changes involve more than one segment, which challenges the explanatory power of the regular phonological approach. Since this approach can account only for single-segment changes, it proves inadequate in such cases. To address this issue, we propose analyzing these loanwords as a syllable truncation, in which foreign suffixes are truncated and replaced with Indonesian suffixes. The loanwords examined in this study are derived from Dutch and were retrieved from the Kamus Besar Bahasa Indonesia (KBBI). The study finds that the Indonesian suffix /tas/ actually replaces the Dutch suffix /-teit/. Truncation, in this context, is treated as a form of reduplication, wherein only the root word is copied into the reduplicative morpheme, following the constraint BASE ≠ RED. Importantly, only the reduplicative morpheme needs to appear in the output, followed by the /tas/ suffix. To account for this pattern, the constraints OCP(X) and ALIGN-PROSODIC-STEM are employed in the analysis. This study thus views Indonesian loanwords as undergoing phonological changes of entire syllables rather than individual segments. Furthermore, it treats truncation as a form of reduplication, suggesting a strong relationship between the two processes as interconnected aspects of prosodic morphology.